Electrode assembly and electrochemical device including the same

By using gradient thickness separator membrane and enhanced adhesive layer in lithium-ion batteries, the problem of decreasing adhesion between electrodes and separator membranes in the battery pack in uneven hot pressing areas is solved, and higher battery performance stability and capacity retention are achieved.

JP7656716B2Active Publication Date: 2025-04-03LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023553717
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-13
Filing Date
2023-01-12
Publication Date
2025-04-03
Estimated Expiration
2043-01-12

AI Technical Summary

Technical Problem

During the hot press fixation process of lithium-ion batteries in existing battery packs, the adhesion between the electrode and the separator is reduced in the uneven hot pressing area, resulting in a degradation of battery performance, especially in the charge and discharge cycle, the battery capacity retention and thickness expansion rate are poor.

Method used

Using a separator film with a gradient thickness, the hyalurite layer of the separator film gradually becomes thinner from both ends to the middle, and an adhesive layer is added to the contact area between the electrode and the separator film to improve the overall adhesion between the electrode and the separator film.

Benefits of technology

During the hot press fixation process, the gradient-thick separator film and the enhanced adhesive layer ensure uniform bonding between the electrode and the separator film throughout the battery pack, improve the battery charge and discharge stability and capacity retention rate, and reduce the thickness expansion rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656716000004
    Figure 0007656716000004
  • Figure 0007656716000005
    Figure 0007656716000005
  • Figure 0007656716000006
    Figure 0007656716000006
Patent Text Reader

Abstract

The present invention relates to a separator, an electrode assembly, and an electrochemical device including the same. The separator according to an embodiment of the present invention is used in a zigzag stacking type electrode assembly, and the separator includes a porous substrate made of a polymer material and a porous coating layer including inorganic particles formed on both sides of the porous substrate. The thickness T of the porous substrate increases from both ends of the separator toward the center in the longitudinal direction. s gradually decreases until the total thickness T c increases gradually as it moves toward the center, and the total thickness (T s +T c ) is kept constant.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode assembly and an electrochemical device including the same, and more particularly, to a zigzag stack type electrode assembly and a secondary battery including the same.

[0002] This application claims priority to Korean Patent Application No. 2022-0005284, filed on January 13, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] Secondary batteries can be classified according to the structure of the electrode assembly, which has a positive electrode / separator / negative electrode structure, and can be broadly divided into a jelly roll (wound type) electrode assembly in which a long sheet-like positive electrode and negative electrode are wound with a separator sandwiched between them, and a stack type (laminated type) electrode assembly in which a plurality of positive electrodes and negative electrodes cut into units of a predetermined size are stacked in sequence with a separator sandwiched between them. However, such conventional electrode assemblies have several problems.

[0004] First, since the jelly roll electrode assembly is formed by winding long sheet-like positive and negative electrodes in a dense state to form a cylindrical or elliptical structure in cross section, stress caused by the expansion and contraction of the electrodes during charging and discharging accumulates inside the electrode assembly, and when the accumulation of such stress exceeds a certain limit, the electrode assembly is distorted. The distortion of the electrode assembly causes the spacing between the electrodes to vary, leading to a rapid deterioration in battery performance and an internal short circuit that threatens the safety of the battery. In addition, since the long sheet-like positive and negative electrodes must be wound, it is very difficult to quickly wind them while maintaining a constant spacing between the positive and negative electrodes, which also leads to a problem of reduced productivity.

[0005] Secondly, since a stack-type electrode assembly requires a plurality of positive and negative electrode units to be stacked in sequence, a separate electrode plate delivery process is required for manufacturing the units. In addition, the sequential stacking process takes a great deal of time and effort, resulting in low productivity.

[0006] FIG. 1 is a cross-sectional view that illustrates a schematic structure of a stacked electrode assembly.

[0007] Referring to FIG. 1, a stack-type electrode assembly 1 has been developed, in which a positive electrode 5 and a negative electrode 7 are stacked in a zigzag pattern with a separator 3 sandwiched between them.

[0008] After assembling the electrode assembly using the zigzag stacking method, a battery is manufactured by fixing the electrode assembly through a final hot press process. In this case, since a large amount of heat and pressure is transferred to the most peripheral region of the electrode assembly that the hot press abuts, there is a problem that the adhesive strength between the electrodes and the separator inside the electrode assembly is relatively reduced in the final hot press process, which ultimately causes a quality defect of the electrode assembly. Summary of the Invention [Problem to be solved by the invention]

[0009] Therefore, an object of the present invention is to provide a separator and a novel structure of an electrode assembly including the same, in which the adhesive strength between the electrode and the separator is maintained at a constant level when manufacturing an electrode assembly using a zig-zag stacking (ZZS) method.

[0010] Specifically, the present invention aims to provide a separator that can exhibit excellent adhesive strength between an electrode and a separator even in an inner region of an electrode assembly where heat and pressure are transferred less than in the upper and lower end regions of the electrode assembly in a stacking direction where the hot press contacts during hot pressing for manufacturing the electrode assembly, and a novel structure of an electrode assembly including the same. [Means for solving the problem]

[0011] In order to solve the above problems, According to one aspect of the present invention, there is provided a separator having the following features.

[0012] According to the first aspect, A separator including a porous substrate made of a polymer material and a porous coating layer including inorganic particles formed on both sides of the porous substrate, the thickness T of the porous substrate increasing from both ends toward the center of the separator in the longitudinal direction. s gradually decreases until the total thickness T c increases gradually as it moves toward the center, and the total thickness (T s +T c ) is provided with a separator that keeps it constant.

[0013] According to the second aspect, The thickness T of the porous substrate is measured from the center (C) of the separator in the longitudinal direction to a predetermined position (A) in the direction of one end and a predetermined position (A') in the direction of the other end. s is kept constant, The entire or at least a part of the region (AE) from the position (A) to one end (E) and the region (A'E') from the position (A') to the other end (E') each have a thickness T of the porous substrate gradually decreasing toward the center of the separator. s gradually decreases until the total thickness T c increases proceeding towards the centre.

[0014] According to a third aspect, the separator may be as described in the first or second aspect, in which the porous coating layers formed on both sides of the porous substrate are formed symmetrically with respect to each other with respect to the center of the longitudinal direction of the separator, and the thicknesses of the porous coating layers at the same arbitrary position perpendicular to the longitudinal direction of the separator are the same as each other or the difference in thickness is within 10%.

[0015] According to a fourth aspect, The separator is formed to have a symmetrical structure with respect to a center (C) in a longitudinal direction, In the region (AE) and the region (A'E'), the thickness T of each of the porous substrates formed at arbitrary positions at the same distance from the center (C) in the longitudinal direction of the separator s may be the separator according to any one of the first to third embodiments, in which the thicknesses are the same as each other or have a difference in thickness of within 10%.

[0016] According to the fifth aspect, The total thickness T of the porous coating layer over the entire surface of the separator c The thickness T of the porous substrate s The ratio (T s / T c ) is 0.5 to 5.

[0017] According to the sixth aspect, The total thickness T of the porous coating layer at the position (A) c The thickness T of the porous substrate s The ratio (T s / T c ) is 1 to 5, the separator may be according to any one of the first to fifth embodiments.

[0018] According to another aspect of the present invention, there is provided an electrode assembly having the following features.

[0019] According to the seventh aspect, An electrode assembly is provided, which includes a unit electrode and a rectangular separator, the separator being folded in a zigzag shape, the unit electrode being inserted into a portion where the separator overlaps, and the separator being the separator according to any one of the first to sixth aspects.

[0020] According to an eighth aspect, The thickness T of the porous substrate is measured from the center (C) of the separator in the longitudinal direction to a predetermined position (A) in the direction of one end and a predetermined position (A') in the direction of the other end. s is kept constant, and the whole or at least a part of the region (AE) from the position (A) to one end (E) and the region (A'E') from the position (A') to the other end (E') are located at the uppermost end and the lowermost end of the electrode assembly in the lamination direction, respectively, and the thickness T s gradually decreases until the total thickness T of the porous coating layer c The electrode assembly may be as described in the seventh embodiment, wherein:

[0021] According to a ninth aspect, The region (AA') from the position (A) to the position (A') is not located at the top or bottom of the electrode assembly in the stacking direction, and the thickness T of the porous substrate is smaller than the thickness T of the separator in the stacking direction of the electrode assembly. s The electrode assembly may be the electrode assembly according to the seventh or eighth aspect, in which

[0022] According to a tenth aspect, The electrode assembly may be the electrode assembly according to any one of the seventh to ninth aspects, in which the adhesive strength between the electrode and the separator at any position of the electrode assembly after being fixed through a hot press process is 20% or more based on the adhesive strength between the electrode and the separator at the topmost position in the stacking direction of the electrode assembly being 100%.

[0023] According to an eleventh aspect, The electrode assembly may be according to any one of the seventh to tenth aspects, in which the adhesive strength between the electrodes and the separator at any position of the fixed electrode assembly is 20 gf / 25 mm or more.

[0024] According to a twelfth aspect, After being fixed through the hot press process, The electrode assembly may be according to any one of the seventh to eleventh embodiments, wherein the separator has lower air permeability at a central portion than at both end portions in the longitudinal direction.

[0025] According to a thirteenth aspect, The separator has a thickness T of a porous substrate from a center (C) in the longitudinal direction to a predetermined position (A) in one end direction and a predetermined position (A') in the other end direction. s is kept constant, and the thickness T of the porous substrate is decreased toward the center of the separator in the entire region (AE) from the position (A) to one end (E) and the entire region (A'E') from the position (A') to the other end (E'), respectively. s gradually decreases until the total thickness T c increases toward the center, and after being fixed through a hot press process, the air permeability of the region (AA') between the positions (A) and (A') is 50% or more compared to the air permeability of at least one of the regions (AE) and (A'E').

[0026] According to still another aspect of the present invention, there is provided an electrochemical device having the following configuration.

[0027] According to a fourteenth aspect, Aspects 7 to 13 There is provided an electrochemical device in which the electrode assembly according to any one of aspects 1 to 13 is housed in a case.

[0028] According to a fifteenth aspect, The electrochemical device may be the electrochemical device according to a fourteenth embodiment, which is a lithium secondary battery. Effect of the Invention

[0029] According to an embodiment of the present invention, when an electrode assembly is fixed through a hot press process, it may exhibit excellent adhesion between the electrodes and the separator even inside the electrode assembly where less heat and pressure are transferred than to the upper and lower ends in the stacking direction.

[0030] Furthermore, the electrode assembly according to one aspect of the present invention has excellent internal adhesion, which effectively improves the phenomenon of increased interfacial resistance between the electrode and the separator caused by the conventional low adhesion, thereby providing a battery with excellent characteristics in terms of capacity retention and suppression of thickness expansion. [Brief description of the drawings]

[0031] [Figure 1] FIG. 2 is a schematic cross-sectional view of one embodiment of a ZZS-type electrode assembly. [Diagram 2] 1 is a schematic diagram showing the top surface of a rectangular separator according to one embodiment of the present invention. [Diagram 3] 1 is a schematic side view of a rectangular separator according to one embodiment of the present invention. [Figure 4] 1 is a schematic side view of a rectangular separator according to one embodiment of the present invention. [Diagram 5] 1 is a schematic diagram illustrating the structure of an electrode assembly before assembly according to one embodiment of the present invention. [Figure 6] 1 illustrates a schematic diagram of a method for manufacturing an electrode assembly according to one aspect of the present invention. [Figure 7] 1 is a simplified side view showing a structure of a separator according to one embodiment of the present invention when folded in a zigzag shape. [Figure 8] 1 is a simplified side view showing a structure of a separator according to one embodiment of the present invention when folded in a zigzag shape. [Figure 9] 1 is a simplified side view showing a structure of a separator according to one embodiment of the present invention when folded in a zigzag shape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The present invention will be described in detail below.

[0033] In this specification, when a part "comprises" a certain component, this does not mean that other components are excluded, but that other components may also be included, unless otherwise specified.

[0034] In addition, the terms and phrases used throughout this specification, such as "about," "substantially," and the like, when given manufacturing and material tolerances inherent in the stated sense, are used to mean at or near the stated value, and are used to prevent unscrupulous infringers from unfairly taking advantage of the disclosure in which precise or absolute values ​​are stated to further the understanding of the invention.

[0035] Throughout this specification, the term "A and / or B" means "A or B, or both."

[0036] Certain terminology used in the following Detailed Description of the Invention is for ease of description only and is not intended to limit the present invention. Additionally, directional words such as "upper", "lower", "right", "left", "front", "rear", "inside", "outside", etc., refer to directions in the drawings to which reference is made or to directions toward or away from the geometric center of the respective designated device, system and components thereof.

[0037] The present invention relates to a separator for an electrochemical device and an electrode assembly including the separator. The electrochemical device may be a primary battery, a secondary battery, a supercapacitor, an electric double layer capacitor, etc. More specifically, the secondary battery may be a lithium ion secondary battery.

[0038] In one embodiment of the present invention, the separator may be for use in a ZZS type electrode assembly in which unit electrodes are inserted into overlapping portions of the separator that are folded in a zigzag shape, but the use of the present invention is not limited thereto.

[0039] In one embodiment of the present invention, the electrode assembly includes unit electrodes and a rectangular separator, and the separator is folded in a zigzag shape, and the unit electrodes are inserted into the overlapping portions of the separator, forming a ZZS type electrode assembly structure.

[0040] Hereinafter, the separator, the electrode assembly, and each component included in the electrode assembly will be described in more detail with reference to the accompanying drawings.

[0041] The separator includes a porous substrate made of a polymer material and a porous coating layer formed on each of both sides of the porous substrate and containing inorganic particles. The thickness T of the porous substrate increases from the end portion to the center portion of the separator in the longitudinal direction. s gradually decreases until the total thickness T of the porous coating layer c gradually increases to a total thickness (Ts +T c ) is held constant.

[0042] In this specification, the "longitudinal direction" of the separator refers to the direction in which two or more unit electrodes are arranged on the strip-shaped separator. For example, the separator has an aspect ratio of more than 1, and the "longitudinal direction" refers to the longer of the horizontal and vertical lengths of the separator. FIG. 2 is a schematic diagram of a separator according to one embodiment of the present invention. Referring to FIG. 2, the separator according to one aspect of the present invention may have a rectangular shape with an aspect ratio of more than 1, and the longer of the horizontal and vertical lengths of the rectangular shape may be defined as the longitudinal direction. In this case, when manufacturing an electrode assembly using the separator, unit electrodes may be arranged in the horizontal direction (i.e., the longitudinal direction) of the separator.

[0043] In this specification, the "stacking direction" of the electrode assembly refers to the height direction in which the unit cells are stacked when the electrode assembly is folded in a zigzag shape and a unit electrode is inserted into a portion where the separators overlap during assembly.

[0044] In this specification, the term "thickness is kept constant within a specific region" means that when the thickness is measured at any position within the specific region according to the same method, the measured thickness value is within an error range of 5% or less. Specifically, when the deviation of the thickness value at any two positions within the specific region is within 5%, within 4%, within 3%, within 2%, within 1%, or 0% (i.e., no difference), it may be expressed that the thickness is kept constant.

[0045] In this specification, the term "thickness gradually increases in a specific region" refers to a continuous or discontinuous increase in thickness value when the thickness is measured in a specific region according to the same method in a certain direction. The rate at which the thickness value increases may be kept constant within an error range of 5% or may change discontinuously, but the gradual increase in thickness in the specific region may preferably represent a continuous increase in thickness value at a constant rate.

[0046] In this specification, the term "thickness gradually decreases in a specific region" means that when the thickness is measured in a specific region according to the same method in a certain direction, the thickness value decreases continuously or discontinuously. The rate at which the thickness value decreases may be constant within an error range of 5% or may change discontinuously, but the gradual decrease in thickness in the specific region may preferably indicate that the thickness value decreases continuously at a constant rate.

[0047] In this specification, unless otherwise specified, the "thickness" of each component may refer to a value measured using a known thickness gauge capable of measuring the thickness of a battery separator. For example, the thickness gauge may be a VL-50S product manufactured by Mitutoyo Corporation, but is not limited thereto.

[0048] In one embodiment of the present invention, the thickness of the porous substrate may be measured after removing the porous coating layer from the separator, for example, by removing the porous coating layer using a solvent capable of dissolving the porous coating layer contained in the separator, and then measuring the thickness of the remaining porous substrate.

[0049] In one embodiment of the present invention, the thickness of the porous coating layer may be measured by measuring the thickness of the separator and then subtracting the thickness of the porous substrate measured as described above, but the measurement method is not limited thereto.

[0050] In one embodiment of the present invention, the separator may be in the form of a strip.

[0051] In one embodiment of the present invention, the rectangular separator is a long strip-shaped separator having a predetermined width, and specifically may refer to a separator having a rectangular shape with an aspect ratio of 1 or more, specifically, greater than 1. More specifically, the separator may have a length of about 1,000 mm or more.

[0052] 2 is a schematic diagram showing the top surface of a rectangular separator according to an embodiment of the present invention. Referring to FIG. 2, the separator 10 may be defined into a top end region X, a bottom end region Y, and an inner region Z located between the top end region and the bottom end region, which are located at the top or bottom end of the stacking direction when folded in the ZZS manner during the manufacture of an electrode assembly.

[0053] 3 is a schematic side view of a rectangular separator according to one embodiment of the present invention. Referring to FIG. 3, the separator 10 includes a porous substrate 11 and a porous coating layer 12 formed on each of both sides of the porous substrate. In this specification, for ease of explanation, the thickness of the porous substrate is referred to as T s and the total thickness of the porous coating layer is represented as T c In this case, the total thickness T of the porous coating layer is expressed as c is the thickness T of the porous coating layer formed on one surface of the porous substrate. c1 and the thickness T of the porous coating layer formed on the other surface. c2 This indicates the sum of the above.

[0054] Referring to FIG. 4, the separator 10 has a thickness T of a porous substrate from one end 103 or 104 to a predetermined position 101 or 102 in the direction of the longitudinal center line 10a. s gradually decreases until the total thickness T c gradually increases, and the total thickness (T s +T c ) is held constant.

[0055] 4 is a schematic side view of a rectangular separator according to one embodiment of the present invention. Referring to FIG. 4, the separator has a thickness T of a porous substrate from a center 10a in the longitudinal direction to a predetermined position 101 in the direction of one end 103 and a predetermined position 102 in the direction of the other end 104. s The separator includes a region (AA′) in which the thickness T of the porous substrate is kept constant from one end 103 to a predetermined position 101. s The thickness T of the porous substrate from the other end 104 to the predetermined position 102 is gradually decreased (AE). s It includes a region (A'E') where the concentration gradually decreases.

[0056] FIG. 5 is a schematic diagram showing a structure of an electrode assembly 30 before assembly in which unit electrodes 20a, 20b are arranged on a rectangular separator 10 according to an embodiment of the present invention. Referring to the figure, a plurality of first unit electrodes are arranged on one side of the separator so as to be spaced apart from each other by a predetermined distance. The distance between each unit electrode is preferably wider than the width of the first unit electrodes, considering that the separator is folded and each folded side must cover the entire surface of the unit electrodes. Meanwhile, a plurality of second unit electrodes may be arranged in the same shape on the other side of the separator. In this case, the first unit electrodes and the second unit electrodes may be arranged in a staggered manner so as not to overlap at all in a side view. When arranged in a staggered manner as above, it is preferable that the adjacent first and second electrodes are spaced apart by a predetermined distance so as to ensure a gap large enough to allow the separator to be folded. When arranged as above, when the separator is folded, an electrode assembly having a structure in which the first and second electrodes are stacked with the separator sandwiched therebetween is obtained. The first and second unit electrodes have opposite polarities. For example, the first unit electrode may be a positive electrode and the second unit electrode may be a negative electrode, or vice versa.

[0057] Fig. 6 is a schematic diagram showing a method for manufacturing an electrode assembly according to an embodiment of the present invention. Referring to Fig. 6, the separator 10 is folded in a zigzag shape, and unit electrodes 20a and 20b are inserted into the overlapping portions of the separators to stack the separators and unit electrodes. After the unit electrodes are inserted, the stacked structure is pressed to manufacture a ZZS type electrode assembly. When pressure is applied to the electrode assembly 30, the pressure applied to the inner region Z is relatively smaller than that of the uppermost region 40a and the lowermost region 40b, which may cause a problem of reduced adhesive strength between the inner electrode and the separator. Therefore, the present invention may incorporate a new structure into the porous substrate and the porous coating layer in the separator included in the electrode assembly.

[0058] In the electrode assembly according to one aspect of the present invention, the separator has a constant overall thickness over the entire surface, so that the interval at which unit electrodes are arranged and the folding interval during assembly of the electrode assembly can be maintained over the entire surface of the electrode assembly. At the same time, the thickness of the porous substrate gradually decreases from both ends of the separator toward the center line in the longitudinal direction, and the thickness of the porous coating layer formed on each of both sides of the porous substrate gradually increases, so that the adhesive force between the inner electrode and the separator can be well maintained even if the heat and / or pressure applied to the inside is small when heat and / or pressure is applied to the inside through the most end portion during the manufacture of the electrode assembly.

[0059] In one embodiment of the present invention, at least a portion of the region (AA') may be located within the X region and / or the Y region.

[0060] Fig. 7 is a schematic diagram showing a side structure of a separator according to one embodiment of the present invention when folded in a zigzag shape. Referring to Fig. 7, when a predetermined position 101 at which the thickness of the porous substrate starts to increase as it progresses toward an end part at a predetermined distance from the center in the longitudinal direction of the separator 10 is located in the uppermost end region X, and a predetermined position 102 at which the thickness of the porous substrate starts to increase as it progresses toward the other end part is located in the lowermost end region Y, a part of the region (AA') may be located in the uppermost end region X and the lowermost end region Y.

[0061] In another embodiment of the present invention, it may be preferable that the region (AA') is not disposed in the uppermost region X and the lowermost region Y based on the stacking direction of the electrode assembly, and that all or at least a portion of the region (AE) and region (A'E') are disposed in the X region and the Y region.

[0062] Specifically, since the Z region is relatively less affected by heat and / or pressure than the X and Y regions when heat and / or pressure are applied during the manufacture of the electrode assembly, it is preferable that the region (AA') is the same as the Z region or is disposed within the Z region. That is, the X region may be included within the region (AE), and the Y region may be included within the region (A'E').

[0063] Fig. 8 is a schematic diagram showing a side structure of a separator according to another embodiment of the present invention when folded in a zigzag shape. Referring to Fig. 8, the position (A) is a predetermined position 101 where the thickness of the porous substrate decreases from one end of the separator to the center line in the longitudinal direction and starts to remain constant, and is located at the inner end of the uppermost region X based on the stacking direction of the electrode assembly, and the position (A') is a predetermined position 102 where the thickness of the porous substrate decreases from the other end to the center line in the longitudinal direction and starts to remain constant, and is located at the inner end of the lowermost region Y based on the stacking direction of the electrode assembly, so that the entire region (AE) may coincide with the X region and the entire region (A'E) may coincide with the Y region.

[0064] Fig. 9 is a simplified side view of a separator according to another embodiment of the present invention when folded in a zigzag shape. Referring to Fig. 9, the position (A) is a predetermined position 101 where the thickness of the porous substrate decreases from one end of the separator to the center line in the longitudinal direction and starts to be kept constant, and is disposed inwardly at a predetermined distance from the uppermost region X based on the stacking direction of the electrode assembly, and the position (A') is a predetermined position 102 where the thickness of the porous substrate decreases from the other end to the center line in the longitudinal direction and starts to be kept constant, and is disposed inwardly at a predetermined distance from the lowermost region Y based on the stacking direction of the electrode assembly, and each part of the region (AE) and the region (A'E) may include the region X and the region Y, respectively.

[0065] In one embodiment of the present invention, the region (AA') may be present in a length of, for example, 10% to 90%, 15% to 80%, 20% to 60%, or 20% to 50% of the total length of the separator, whereby the region (AE) and the region (A'E') may be present at the end of the separator such that the length excluding the region (AA') from the total length becomes the total length of the region (AE) and the region (A'E').

[0066] In one embodiment of the present invention, the lengths of the regions (AE) and (A'E') may be the same, i.e., the lengths of the regions (AE) and (A'E') may be equal to the total length of the separator excluding the region (AA').

[0067] In one embodiment of the present invention, the regions (AE) and (A'E') are formed from the end portions of the separator toward the center thereof with a thickness T of the porous substrate. s decreases, and the total thickness of the porous coating layer T c By increasing the thickness of the electrode, even if heat and / or pressure is applied to the end portion based on the stacking direction during assembly of the electrode, the adhesive strength between the inner electrode and the separator can be sufficiently exhibited, but the effects of the present invention are not limited thereto.

[0068] In one embodiment of the present invention, the porous coating layers formed on both sides of the porous substrate may be formed symmetrically with respect to a center line 10b in the thickness direction of the separator.

[0069] Referring to Figures 3 and 4, when the porous coating layer formed on the upper surface of the porous substrate is named a first porous coating layer and the porous coating layer formed on the lower surface of the porous substrate is named a second porous coating layer, the first porous coating layer and the second porous coating layer may be formed in a shape that is line-symmetrical with respect to a center line 10b in the thickness direction of the porous substrate.

[0070] Specifically, the porous coating layers formed on both sides of the porous substrate are formed symmetrically with respect to the center line of the separator in the thickness direction, and the thicknesses of the porous coating layers at any position perpendicular to the longitudinal direction of the separator may be the same or may have a thickness difference of within 10%.

[0071] For example, at any position on the porous substrate, the thickness T of the first porous coating layer located on an imaginary line perpendicular to the longitudinal direction of the separator c1 and the thickness T of the second porous coating layer c2 are the same, or if different from each other, the difference in thickness may be within 10%.

[0072] More specifically, the difference between the thicknesses of the first and second porous coating layers may be within 10%, within 8%, within 5%, within 4%, within 3%, within 2%, within 1%, or 0% (i.e., identical).

[0073] In one embodiment of the present invention, the separator may be formed to have a symmetrical structure with respect to a center 10a in the longitudinal direction.

[0074] In one embodiment of the present invention, the separator may be formed to have a symmetrical structure with respect to a center line 10a in the longitudinal direction and a center line 10b in the thickness direction. Referring to Fig. 4, the region (AE) from the predetermined position 101 to the end 103 and the region (A'E') from the other predetermined position 102 to the other end 104 may be formed to have a symmetrical structure with respect to the center line 10a in the longitudinal direction and the center line 10b in the thickness direction.

[0075] Specifically, the separator has a thickness T of the porous substrate formed at an arbitrary position at the same distance from the center line 10a in the longitudinal direction of the separator in the region (AE) and the region (A'E'). smay be identical to one another or may differ in thickness by within 10%.

[0076] More specifically, the thicknesses T of the porous substrates formed at arbitrary positions at the same distance from the center line 10a in the longitudinal direction of the separator in the regions (AE) and (A'E') are s may differ by within 10%, within 8%, within 5%, within 4%, within 3%, within 2%, within 1%, or 0% (i.e., identical).

[0077] In one embodiment of the present invention, the total thickness T of the porous coating layer is c The thickness T of the porous substrate s The ratio (T s / T c ) may be 0.5 to 5. Specifically, the ratio (T s / T c ) may be 0.8 to 3, 1 to 2, or 1 to 1.8. In the electrode assembly, the thickness T s is gradually increase The total thickness T of the porous coating layer c is gradually decrease Therefore, the ratio (T s / T c )teeth increase This shows how the situation changes.

[0078] In another embodiment of the present invention, the total thickness T of the porous coating layer at the position (A) is c The thickness T of the porous substrate s The ratio (T s / T c ) can be 1 to 5. Specifically, the ratio (T s / T c) may be 1 to 3, 1 to 2, or 1.5 to 1.8. In the electrode assembly, as described above, the region (AA') from the position (A) to the position (A') has a thickness T s is kept constant, and the ratio (T s / T c ) is the ratio (T s / T c ) can be shown.

[0079] In one embodiment of the present invention, the porous substrate means a substrate having a large number of pores formed therein, which is an ion-conducting barrier that allows ions to pass while blocking electrical contact between the negative electrode and the positive electrode. The pores are interconnected, allowing gas or liquid to pass from one side of the substrate to the other side. As such a porous substrate, a porous polymer film containing a thermoplastic resin can be used from the viewpoint of providing a shutdown function. Here, the shutdown function refers to a function in which, when the temperature of the battery becomes high, the thermoplastic resin is dissolved to block the pores of the porous substrate, thereby blocking the movement of ions and preventing thermal runaway of the battery. As the thermoplastic resin, a thermoplastic resin having a melting point of less than 200° C. is preferable, and polyolefin is particularly preferable.

[0080] In one embodiment of the present invention, the porosity of the porous substrate may be, for example, 30% to 90%, 35% to 80%, 40% to 70%, 40% to 60%, or 40% to 50%. The porosity of the porous substrate may be, for example, a value measured according to the formula [true density of the material contained in the porous substrate - density of the porous substrate / true density x 100 (%)].

[0081] In one embodiment of the present invention, the thickness of the porous substrate is in the above-mentioned ratio (T s / T c ) is satisfied, it may be, for example, 5 μm to 300 μm.

[0082] In one embodiment of the present invention, the porous coating layer is formed on each of the upper and lower surfaces of the porous substrate and includes inorganic particles. The inorganic particles are densely packed in the porous coating layer, and the porous coating layer may have a large number of micropores due to interstitial volumes formed between the inorganic particles.

[0083] In one embodiment of the present invention, the porous coating layer may further include a binder resin, and the inorganic particles may be coated with the binder resin on all or at least a part of the surface. In this case, the inorganic particles are surface-bound and / or point-bound via the binder resin. For example, the inorganic particles and the binder resin may be included in the porous coating layer in a weight ratio of 95:5 to 50:50.

[0084] In one embodiment of the present invention, the inorganic particles can be used without any particular limitation as long as they are electrochemically stable. That is, the inorganic particles usable in the present invention can be used in the range of operating voltages (e.g., Li / Li + There are no particular limitations as long as the inorganic particles do not undergo oxidation and / or reduction reactions at a potential of 0 V to 5 V relative to the reference potential. Non-limiting examples of such inorganic particles include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT,0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC and TiO2, and one or more of these may be included.

[0085] In one aspect of the present invention, when the porous coating layer includes a binder resin, the binder resin may include, for example, a polyvinylidene fluoride-based resin (PVdF-based resin). In one embodiment of the present invention, the PVdF-based resin may include at least one of a homopolymer of vinylidene fluoride (i.e., polyvinylidene fluoride), a copolymer of vinylidene fluoride and a copolymerizable monomer, and a mixture thereof. In one embodiment of the present invention, the monomer may be, for example, a fluorinated monomer and / or a chlorine-based monomer. Non-limiting examples of the fluorinated monomers include vinyl fluoride, trifluoroethylene (TrFE), chlorofluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro(alkyl vinyl) ethers such as perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE) and perfluoro(propyl vinyl) ether (PPVE), perfluoro-1,3-dioxole, and perfluoro(2,2-dimethyl-1,3-dioxole) (PDD), and the like, and may include one or more of these.

[0086] In one embodiment of the present invention, the PVdF-based resin may have a Tm of 140° C. or less in terms of adhesive strength during heat bonding. For this purpose, the PVdF-based resin may contain a copolymer of vinylidene fluoride units and other monomers copolymerizable with the vinylidene fluoride units. Examples of such copolymers include PVDF-TrFE, PVDF-TFE, PVDF-CTFE, and PVDF-HFP, and the resin may contain one or more of these.

[0087] Meanwhile, the binder resin may further include a (meth)acrylic polymer resin in addition to the PVDF-based resin, if necessary. The (meth)acrylic polymer contains a (meth)acrylic acid ester as a monomer, and non-limiting examples thereof include (meth)acrylic polymers containing butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-oxyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate as monomers.

[0088] In one embodiment of the present invention, the separator may be manufactured by a method of coating a porous substrate with a slurry for forming an inorganic coating layer containing the inorganic particles or the binder resin and inorganic particles, and drying the solvent and / or the binder resin to integrally form a porous coating layer on the porous substrate. The manufacturing method of the separator may be applied without any restrictions as long as the porous coating layer is formed on each of the upper and lower surfaces of the porous substrate and the separator having the above-mentioned shape can be obtained, and is not limited to a specific manufacturing method.

[0089] In one embodiment of the present invention, the thickness of the porous coating layer is set to the above-mentioned ratio (T s / T c ) is satisfied, it may be, for example, 3 μm to 50 μm.

[0090] The electrode assembly according to the present invention includes a separator having the above-mentioned shape, and a pair or more of unit electrodes spaced apart from each other on the separator.

[0091] In one aspect of the present invention, the unit electrode may be a typical positive electrode and / or negative electrode used in an electrochemical device, and the positive electrode and the negative electrode may each be a current collector coated with an electrode active material, and the size and shape of the unit electrode are not particularly limited.

[0092] When the electrode is a positive electrode, the positive electrode active material may be, for example, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide obtained by combining these, or a mixture of two or more of these, but is not limited thereto.

[0093] When the electrode is a negative electrode, examples of the negative electrode active material that can be used include, but are not limited to, lithium metal or lithium alloy, soft carbon, hard carbon, natural graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, petroleum or coal tar pitch derived cokes, or a mixture of two or more of these.

[0094] The electrode assembly according to the present invention having the above-mentioned structure can exhibit an effect of excellent shape retention since pressure is applied in a stacking direction of the electrode assembly through a hot pressing process, which remarkably improves heat resistance and impact resistance of the electrode assembly.

[0095] In one embodiment of the present invention, after being fixed through a hot press process, the adhesive strength of the electrode and separator at any position of the electrode assembly may be 20% or more based on the adhesive strength of the uppermost electrode and separator at 100% based on the stacking direction of the electrode assembly.

[0096] In one embodiment of the present invention, the hot pressing step may be carried out by applying a pressure of 3 MPa to 10 MPa to the electrode assembly at a temperature of 50°C to 110°C, for example.

[0097] In another aspect of the present invention, the hot pressing process may be performed by applying a pressure of 10 tons at a temperature of 90° C. for 15 seconds. In this case, after being fixed through the hot pressing process, the adhesive strength of the electrode and the separator at any position of the electrode assembly may be 20% or more based on the adhesive strength of the electrode and the separator at the topmost position in the stacking direction of the electrode assembly being 100%.

[0098] In yet another aspect of the present invention, after the fixing, the adhesive strength of the electrode and separator at any position of the electrode assembly may be specifically 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, and more specifically 90% or more, based on the adhesive strength of the uppermost electrode and separator in the stacking direction of the electrode assembly being 100%.

[0099] In this specification, the adhesive strength of the electrode and separator of the electrode assembly after being fixed through the hot pressing process may be measured by performing a peel evaluation using a universal testing machine (UTM) (manufactured by Instron Corp.) In particular, in the electrode assembly hot pressed according to the above method, a width of 25 mm based on the separator is sampled, and the peel strength of the electrode and separator is evaluated using the universal testing machine under conditions of 180° peel and 300 mm / min.

[0100] In one embodiment of the present invention, the adhesive strength between the electrodes and the separator at any position of the electrode assembly fixed as described above may be 20 gf / 25 mm or more.

[0101] In other aspects of the present invention, the adhesive strength of the electrodes and separators at any position of the electrode assembly fixed as described above can be, for example, 30 gf / 25 mm or more, 40 gf / 25 mm or more, 50 gf / 25 mm or more, 60 gf / 25 mm or more, 70 gf / 25 mm or more, 80 gf / 25 mm or more, and more specifically, 90 gf / 25 mm or more and 100 gf / 25 mm or less.

[0102] In one aspect of the present invention, the separator used in the electrode assembly fixed as described above may have lower air permeability at a central portion than at both ends in a longitudinal direction.

[0103] If a conventional separator having a uniform thickness of the porous substrate and the porous coating layer is used instead of the separator according to one aspect of the present invention, the air permeability of the separator region located in the inner region based on the stacking direction is significantly lower than that of the separator region located in the uppermost region and / or the lowermost region based on the stacking direction of the electrode assembly when the electrode assembly is heat fixed, resulting in variation in air permeability. However, if the separator according to one aspect of the present invention is used, the air permeability of the uppermost region and / or the lowermost region based on the stacking direction of the electrode assembly is also lowered to the level of the inner region when the electrode assembly is heat fixed, thereby reducing the variation in air permeability. Thus, if the air permeability is high, it is possible to effectively improve the problems of the decrease in output of the battery using the separator and the decrease in performance due to repeated charge and discharge cycles, but the effects of the present invention are not limited thereto.

[0104] In one embodiment of the present invention, the separator has a thickness T of the porous substrate from the center (C) in the longitudinal direction to a predetermined position (A) in the direction of one end and a predetermined position (A') in the direction of the other end. sis kept constant, and the thickness T of the porous substrate is decreased toward the center of the separator in the entire region (AE) from the position (A) to one end (E) and the entire region (A'E') from the position (A') to the other end (E'), respectively. s gradually decreases until the total thickness T of the porous coating layer c increases toward the center, after the electrode assembly is heat-set, the air permeability of the region (AA') between the positions (A) and (A') may be 50% or more as compared to the air permeability of at least one of the regions (AE) and (A'E'), where the heat-set conditions are as described above.

[0105] More specifically, after the electrode assembly is heat fixed, the air permeability of the region (AA') may be 50% to 100%, 55% to 99%, 60% to 95%, 70% to 95%, 80% to 95%, 85% to 95%, or 90% to 95%, or 91%, compared to the air permeability of at least one of the regions (AE) and (A'E').

[0106] In this specification, the air permeability (Gurley) of the separator may be measured by the ASTM D726-94 method. The Gurley used herein is the resistance to air flow and may be measured by a Gurley densometer. Specifically, the measured air permeability value is the value of the air permeability measured by measuring the air permeability of the separator under a pressure of 12.2 inches of water (in H2O) with 100 cc of air per square inch (in2). 2 For example, according to one embodiment of the present invention, the air permeability can be measured using an EG01-55-1MR device manufactured by Asahi Seiko Co., Ltd.

[0107] In one embodiment of the present invention, the electrode assembly fixed as described above may exhibit a capacity retention rate of 80% or more, for example, 90% or more, or 95% or more after 500 charge / discharge cycles, although the present invention is not limited thereto.

[0108] In one embodiment of the present invention, the electrode assembly fixed as described above may exhibit a thickness of 110% or less, for example, 105% or less, of the initial thickness after 500 charge / discharge cycles, although the present invention is not limited thereto.

[0109] In one embodiment of the present invention, the electrochemical device includes the above-described electrode assembly housed in a case.

[0110] In one embodiment of the present invention, the case may be any commonly used battery case, and is not particularly limited in shape depending on the intended use of the battery. For example, the case may be a cylindrical case using a can, a square case, a pouch case, or a coin case.

[0111] Once the electrode assembly is completed, it can be housed in a case and sealed in a conventional manner to manufacture an electrochemical device, which can be, for example, a lithium secondary battery.

[0112] The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples.

[0113] Example 1 [Separator manufacturing] The separator was manufactured according to the following method.

[0114] For each component, the porosity was measured according to the formula: [(true density of applied material-density of the component) / true density x 100(%)].

[0115] The thickness of each component was measured using a thickness measuring device (VL-50S, manufactured by Mitutoyo Corporation).

[0116] Preparation of the Porous Substrate Three polyethylene polymers and polypropylene polymers with different molecular weights were mixed with an antioxidant in an appropriate ratio to prepare a porous substrate for use in a separator according to a known method. The three polyethylene polymers used were PE 40 (Mw 400,000 g / mol), PE 90 (Mw 900,000 g / mol) and PE 150 (Mw 1,500,000 g / mol), and the polypropylene polymer was PP 35 (Mw 350,000 g / mol). The porosity of the prepared porous substrate was 45%.

[0117] The porous substrate had an overall width of 350 mm and a length of 1 m, and the thickness measured at both ends was 15 μm. The thickness gradually decreased from both ends to a point 0.3 m in the longitudinal direction, and the thickness was maintained at 12 μm from the 0.3 m point.

[0118] Fabrication of the porous coating layer A slurry for inorganic coating was prepared by mixing poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) binder (Mw 500,000 g / mol, HFP 15 wt%) and inorganic particles in a weight ratio of 80:20 in a suitable solvent.

[0119] The inorganic coating slurry prepared above was applied to the entire surface of the porous substrate by dip coating and dried according to the vapor-induced phase separation method (VIPS) to form a porous coating layer on each of the upper and lower surfaces of the porous substrate prepared above.

[0120] The porous coating layers formed on the upper and lower surfaces each had a thickness of 4.5 μm measured at both ends, and the thickness gradually increased from both ends to a point 0.3 m in the longitudinal direction, and the thickness was maintained at 6 μm from the 0.3 m point.

[0121] This produced a separator with a consistent overall thickness of 24 μm across its entire surface.

[0122] [Manufacturing of electrode assemblies] An electrode assembly was manufactured using the separator prepared as described above. Specifically, 17 positive electrodes and 16 negative electrodes were arranged crosswise on the upper and lower surfaces of the separator. At this time, the point where the end of the positive electrode was located on one side and the point where the end of the negative electrode was located on the other side were arranged crosswise with a horizontal distance of 3 mm on a plane. Lithium cobalt oxide (LCO) was used as the positive electrode active material, and graphite was used as the negative electrode active material (N / P ratio>100).

[0123] Comparative Example 1 [Separator manufacturing] Preparation of the Porous Substrate A porous substrate was produced in the same manner as in Example 1, except that the thickness was constant at 15 μm without any change in thickness over the entire length direction.

[0124] Fabrication of the porous coating layer A porous coating layer was formed in the same manner as in Example 1, except that the thickness was constant at 9 μm without any change in thickness over the entire length direction, thereby producing a separator with a constant thickness of 24 μm.

[0125] [Manufacturing of electrode assemblies] An electrode assembly was produced in the same manner as in Example 1, except that the separator produced above was used.

[0126] [Evaluation of adhesive strength after hot pressing process] The electrode assembly manufactured above was pressed for 15 seconds under conditions of 90°C and 10 tons using a hot press device, and then a separator width of 25 mm was sampled from the cell to be evaluated.Then, a universal testing machine (UTM) (manufactured by Instron) was used to measure the force required to peel the electrode and separator under conditions of 180° peel and 300 mm / min, and the results are shown in Table 1 below.

[0127] The adhesive strength was measured at each of the endmost and central parts of the electrode assemblies prepared as described above in Example 1 and Comparative Example 1. In this regard, the adhesive strength at the endmost part was evaluated by measuring the adhesive strength between the electrodes and separator of the unit cell located at the top end of the fixed electrode assembly, and the adhesive strength at the central part was evaluated by measuring the adhesive strength between the electrodes and separator of the unit cell located at the center of the fixed electrode assembly.

[0128] [Table 1]

[0129] As is apparent from Table 1 above, it was confirmed that Comparative Example 1 after hot pressing had a very large difference in adhesive strength between the central electrode and the separator, whereas Example 1 exhibited excellent adhesive strength throughout the entire electrode assembly.

[0130] [Evaluation of breathability] In order to evaluate the change in air permeability after hot pressing of the separators produced in Example 1 and Comparative Example 1 above, the separators produced in Example 1 and Comparative Example 1 above were pressed for 15 seconds under conditions of 90°C and 10 tons using a hot press device.

[0131] Next, the air permeability was measured in the regions from both ends of the hot-pressed separator to points 0.3 m in the longitudinal direction (endmost portions) and in the region between the points 0.3 m from both ends (center portion).

[0132] Specifically, the air permeability is calculated per square inch (in 2 ) was measured using an EG01-55-1MR device manufactured by Asahi Seiko Co., Ltd., and the average values ​​of the measurement results of the air permeability of six regions for each of the extreme end and central regions are shown in Table 2 below.

[0133] [Table 2]

[0134] As is clear from Table 2 above, after hot pressing, the variation in air permeability in the central portion was significant compared to the extreme end portion of the separator of Comparative Example 1, whereas the variation in air permeability in the central portion was significantly reduced compared to the extreme end portion of the separator of Example 1.

[0135] [Battery performance evaluation] 500 charge / discharge cycles were performed using an electrochemical charger / discharger. At this time, charging was performed at a current density of 0.1 C-rate up to a voltage of 4.3 V, and discharging was performed at the same current density up to 2.5 V. The capacity retention rate and thickness expansion rate were evaluated as follows.

[0136] The target property for capacity retention is that the capacity after 500 cycles is 80% or more of the initial capacity, and the target property for thickness expansion rate is that the thickness after 500 cycles is 110% or less of the initial thickness.

[0137] Capacity retention (%) = (Capacity after 500 cycles / Initial capacity) x 100 As described above, the volume retention and thickness expansion were evaluated, and the results are shown in Table 3 below.

[0138] [Table 3]

[0139] As is apparent from Table 3 above, it was confirmed that in terms of suppressing capacity degradation and thickness expansion, Example 1 exhibited superior effects compared to Comparative Example 1. In particular, it was confirmed that the use of the electrode assembly of Comparative Example 1 did not satisfy the target physical properties in terms of capacity degradation rate and thickness expansion rate.

[0140] This is presumably because the internal adhesive strength of Comparative Example 1 was poor, which caused an increase in resistance between the electrode and the separator and an expansion in thickness.

[0141] The present invention has been described above based on the embodiments and drawings. However, a person having ordinary knowledge in the technical field to which the present invention pertains should be able to make various applications and modifications within the scope of the present invention based on the above content. [Explanation of symbols]

[0142] 1 Electrode assembly 3. Separator 5 Positive electrode 7 Negative electrode 110 Separator 11 Porous substrate 12 Porous coating layer 10a Separator longitudinal center 10b Center of separator thickness 20a negative electrode 20b positive electrode 30 Electrode assembly 40 Pressing process of electrode assembly 40a: Uppermost region of the electrode assembly 40b Lowermost region of electrode assembly 101 Position (A) 102 Position (A') 103 Position (E) 104 Position (E') X Top end area based on stacking direction Y: Bottom end area based on stacking direction Inner area based on Z layer direction T s Porous substrate thickness T c1 , T c2 Porous coating layer thickness

Claims

1. A battery comprising a unit electrode and a rectangular separator, The separator is folded in a zigzag shape, and the unit electrodes are inserted into overlapping portions of the separator, The separator is A porous substrate made of a polymer material; a porous coating layer formed on each of both sides of the porous substrate and including inorganic particles; Including, The thickness of the porous substrate (T s ) gradually decreases, and the total thickness (T c ) increases gradually toward the center, The separator has an overall thickness (T s +T c ) is kept constant, the thickness (Ts) of the porous substrate is kept constant from the center (C) in the longitudinal direction of the separator to a predetermined position (A) in the direction of one end and to a predetermined position (A') in the direction of the other end; The whole or at least a part of the region (AE) from the position (A) to one end (E) and the region (A'E') from the position (A') to the other end (E') are respectively disposed at the uppermost end and the lowermost end in the lamination direction of the electrode assembly, and the thickness (Ts) of the porous substrate gradually decreases as it progresses toward the center of the separator, and the total thickness (Tc) of the porous coating layer increases as it progresses toward the center, The region (AA') from the position (A) to the position (A') is not located at the top end or the bottom end based on the stacking direction of the electrode assembly, An electrode assembly, wherein a thickness (Ts) of the porous substrate decreases toward a center of the separator in regions of the separator that are disposed at the uppermost and lowermost ends in a stacking direction of the electrode assembly.

2. 2. The electrode assembly of claim 1, wherein the porous coating layers formed on both sides of the porous substrate are formed symmetrically with respect to a center portion of the separator in a longitudinal direction, and the thicknesses of the porous coating layers at any position perpendicular to the longitudinal direction of the separator are the same or have a thickness difference of within 10%.

3. The separator is formed to have a symmetrical structure with respect to the center (C) in the longitudinal direction, In the region (AE) and the region (A'E'), the thickness (T s 2. The electrode assembly according to claim 1, wherein the thicknesses of the first and second electrodes are the same or have a thickness difference of within 10%.

4. The total thickness (T c ) to the thickness of the porous substrate (T s ) ratio (T s / T c 2. The electrode assembly according to claim 1, wherein the ratio of the surface area to the surface area of ​​the electrode is 0.5 to 5.

5. The total thickness (T c ) to the thickness of the porous substrate (T s ) ratio (T s / T c 2. The electrode assembly according to claim 1, wherein n is an integer from 1 to 5.

6. 2. The electrode assembly of claim 1, wherein after being fixed through a hot press process, an adhesive strength between the electrode and the separator at any position of the electrode assembly is 20% or more based on an adhesive strength between the electrode and the separator at an uppermost position in a stacking direction of the electrode assembly being 100%.

7. 7. The electrode assembly according to claim 6, wherein the adhesive strength between the electrodes and the separator at any position of the fixed electrode assembly is 20 gf / 25 mm or more.

8. After being fixed through a hot press process, The electrode assembly according to claim 1 , wherein the separator has a lower air permeability at a central portion than at both ends in a longitudinal direction of the separator.

9. The separator is fixed through a hot press process, The electrode assembly of claim 1, wherein the air permeability of the region (AA') between the positions (A) and (A') is 50% or more compared to the air permeability of at least one of the regions (AE) and (A'E').

10. An electrochemical device comprising the electrode assembly according to claim 1 housed in a case.

11. The electrochemical device according to claim 10 , wherein the electrochemical device is a lithium secondary battery.

Citation Information

Patent Citations

  • Method of Manufacturing Separator for Electrochemical Devices

    KR1020170087136A

  • Separator Including Nonflammable layer with Thick Thickeness

    KR1020210026537A

  • Lithium secondary battery and production method for same

    WO2011155060A1